Yield Responses of Wheat to Mulching Practices in Dryland Farming on the Loess Plateau - Wang, Li-fang; Chen, Juan; Shangguan, Zhou-ping (PloS one, 2015)
Improving farming practices of soil and water conservation has profound effects on the yield of wheat (Triticum aestivum L.) in dryland farming regions of the Loess Plateau in China. Mulching has proven to be an effective practice to increase crop yield, and possibly contribute to replenishing groundwater. This evaluation study collected and analyzed the data of 1849 observations published in 38 papers using meta-analysis to investigate effects of the mulching practices on wheat yield in terms of different rainfall and regions in comparison with conventional tillage. The main results of the study follow. The effects of the mulching practices were ranked in the order of RFM (ridge-furrow mulching) > MTMC (mulching with two materials combined) > MOM (mulching with other materials) > WSM (wheat straw mulching) > FM (flat mulching). The effects of the mulching practices at the different levels of rainfall during the wheat growing season were in the order: (< 150 mm) > (> 250 mm) > (150-250 mm). The effects of the mulching practices in the different regions were in the order of Henan > Shanxi > Shaanxi > Gansu. WSM, MTMC and FM performed better in improving wheat yield for rainfall of < 150, 150-250 and > 250 mm during the growing season, respectively. The wheat yield with FM, MTMC, MOM and MOM was higher than those with the other mulching practices in Shaanxi, Gansu, Henan and Shanxi. The wheat yield with RFM was 27.4% higher than that with FM, indicating that RFM was the most effective practice to improve wheat yield among all the practices. These findings have important implications for choosing appropriate crop field management to improve wheat yield.